Linguistic incentive category: definition and classification: example of different systematic languages - Muminova, Aziza Arslonovna (Linguistics and Culture Review, 2021)
The article discusses the difference between the category of motivation and the modality, that is, it is a type of speech act in which the speaker’s wishes, desires, wills, and intentions are given to the listener. While modality refers to the speaker’s response to the content of a sentence, the urge is expressed as the speaker’s command to the listener. The reason why motivation is separated from modality as a separate category is that it combines several elements under a common motivational semaphore, which on the one hand motivates the addressee to do something as part of a complex whole, but on the other hand they do not intersect. Each component has its own specific motivation, for example: command, request, permission, prohibition, advice, warning, and so on. Motivation as an independent category has a communicative semantic tone and its own structure. The structure of the motivation category consists of a combination of content, transmission, and expression. The content side consists of communicative pragmatic and semantic components, the delivery plan consists of a field of language units that reflect the meaning of the impulse, and the expressive aspect consists of phonological, intonation and graphic parts.